Controlled diffusion by thin layer coating: The intricate case of the glass-stopper interface. (February 2021) - Chanut, Julie; Bellat, Jean-Pierre; Gougeon, Régis D.; Karbowiak, Thomas
Abstract: A comprehensive study was carried out to investigate the critical role played by the interface between the stopper and the bottleneck on oxygen penetration into the bottle, as well as the effect of surface treatment of the stopper. First, the compression of micro-agglomerated cork, at close to 40% (similar to that of a cork stopper in a still wine bottleneck), had a very limited effect on the oxygen transfer. Second, once a cork was inserted into a glass bottleneck without any surface treatment, up to 99% of the total oxygen transfer took place at the stopper-bottleneck interface. Third, when the cork surface was coated with a paraffin-silicone mixture, there was almost no oxygen transfer at the interface. Although initially used as a slippery agent for easier uncorking, the surface coating of the stopper, as a thin layer of several hundred nanometers, had a remarkable and unexpected impact on the control of the oxygen transfer. Graphical abstract: Image 1 Highlights: Stopper-bottleneck interface plays a critical role in the oxygen transfer. Compression of agglomerated cork for still wine reduced oxygen diffusion by 35%. Stopper surface coating has a remarkable impact on the oxygen transfer control.